Effects of Integrated Therapeutic Exercises on Pain and Disability in Medial Knee Osteoarthritis - Sumit Raghav; Anshika Singh; Suresh Mani; Anirudh Srivastava; Mukul Kumar (Central European Journal of Sport Sciences and Medicine, 2023)
The purpose of this study was to compare the effect of quadriceps isometric exercises along with hip abductors isometric exercises as integrated exercise with quadriceps exercises in reducing pain, disability in medial knee osteoarthritis. The Total of 54 patients (both male and female) were recruited in this study but on the basis of inclusion and exclusion criteria, only 32 were included in this study. Womac index was opted as outcome measures to collect the data of pain, disability and functional limitation. Participants were randomly assigned to integrated exercise group; (n = 16) (mean age 52) who performed exercises [Quadriceps isometric along with hip abductor isometric exercises] and quadriceps isometric exercises group (n = 16) (mean age 49) performed for 3 weeks. 32patients were analyzed and the effect of integrated exercises [Quadriceps isometric along with hip abductor isometric exercises] showed a statistically significant difference in pain, disability and functional limitation (p < 0.000). Total duration to collect the pre and post data of pain, disability and functional limitation was 3 weeks. 3 weeks of exercise protocol was effective in both groups in terms of reducing pain and disability but integrated exercises were found to be more effective than quadriceps exercise in improving the pain, disability and functional limitation over the time at the level of significance.